PENGARUH UKURAN PERUSAHAAN DAN KOMITE AUDIT TERHADAP FINANCIAL DISTRESS - Muhammad Ikhsan Febriyanto; Siti Nurul Fathimah; Desi Kurniawati (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to examine the effect of firm size and audit committee on financial distress in banking sector companies. Financial distress is proxied by financial ratios, firm size is measured using the natural logarithm of total assets, and the audit committee is measured by the number of audit committee members. The study employs secondary data obtained from annual financial statements of banking companies listed on the Indonesia Stock Exchange, with a total of 105 observations. Panel data regression analysis is conducted using EViews software, and the best estimation model is selected through the Chow test and Hausman test. The results indicate that firm size has a significant negative effect on financial distress, suggesting that larger firms tend to have lower financial distress risk. Meanwhile, the audit committee has a significant positive effect on financial distress, highlighting the important role of audit committees in strengthening corporate oversight and financial transparency. Simultaneously, firm size and audit committee significantly affect financial distress. These findings imply that strengthening corporate governance mechanisms and optimizing asset management are crucial in mitigating financial distress risk in the banking sector.